A three-component difunctionalization of N-alkenyl amides via organophotoredox radical-polar crossover. Issue 68 (5th August 2022) - Dhungana, Roshan K.; Granados, Albert; Sharique, Mohammed; Majhi, Jadab; Molander, Gary A.
Abstract : Herein, we report a three-component organophotoredox coupling of N -alkenyl amides with α-bromocarbonyls and various nucleophiles. Abstract : Herein, we report a three-component organophotoredox coupling of N -alkenyl amides with α-bromocarbonyls and various nucleophiles. This transition metal-free difunctionalization protocol installs sequential C–C and C–Y (Y = S/O/N) bonds in alkenes. This reaction works with terminal and internal alkenes containing both cyclic and acyclic amides via radical-polar crossover.